Importance of Assertiveness and Self Esteem among Nursing Students: Examining the Impact of Assertiveness Training on Nursing Students (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Training in assertiveness is useful in boosting nursing students' confidence and assertiveness.Boosting one's confidence and assertiveness with the help of this non-invasive, drug-free alternativetreatment is both effective and affordable. Training in assertiveness has been shown to have positiveeffects on people's health. The results of the study show that training courses created with these goalsin mind are successful in raising participants' assertiveness, confidence, and conduct. Positive changesin self-perception, happiness, academic performance, and social engagement have also been observedas a result of these programs. Study is required to probe the socio-psychological effects ofassertiveness instruction.